2021
DOI: 10.1016/j.heliyon.2021.e08477
|View full text |Cite
|
Sign up to set email alerts
|

Impact of meteorological parameters on mosquito population abundance and distribution in a former malaria endemic area, central Iran

Abstract: Populations of mosquitoes were larger during the dry months. The mean monthly temperature below 30 C was most suitable for mosquitoes. There was a non-significant relationship between wind speed and mosquitoes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 38 publications
2
12
0
Order By: Relevance
“…minimus densities to the relative humidity only. There was a similar correlation reported between nightly abundance of Anopheles species with relative humidity (range: 27.00–56.40%) and ambient temperature (range: 29.20 °C–30.00 °C) during the peak biting period ( Asgarian, Moosa-Kazemi & Sedaghat, 2021 ). Significant direct correlations of paired An.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…minimus densities to the relative humidity only. There was a similar correlation reported between nightly abundance of Anopheles species with relative humidity (range: 27.00–56.40%) and ambient temperature (range: 29.20 °C–30.00 °C) during the peak biting period ( Asgarian, Moosa-Kazemi & Sedaghat, 2021 ). Significant direct correlations of paired An.…”
Section: Discussionsupporting
confidence: 76%
“…For example, temperature and wind movement can influence mosquito activity patterns ( Bowen, 1991 ), abundance ( Ram et al, 1998 ; Wu et al, 2007 ), and survival ( Ciota et al, 2014 ). An increase in environmental temperature was associated with increased host seeking activity of Culex pipiens, Aedes detritus and Aedes caspius ( Drakou et al, 2020 ) and Anopheles populations ( Asgarian, Moosa-Kazemi & Sedaghat, 2021 ). Therefore, it accelerated the blood digestion, increased human biting frequency, shortened the gonotrophic cycle of An.…”
Section: Discussionmentioning
confidence: 99%
“…The Intergovernmental Panel on Climate Change (IPPC, 2018) has indicated that mosquito-borne diseases (MBDs) will be particularly impacted by climate change. Indeed, seasonal variations in the occurrence and abundance of mosquito populations are intricately tied to climatic factors, which in turn impact their vector potential [ 3 ]. In Canada, the burden of MBDs has increased by 10% in the past 20 years and is expected to continue to rise if the impacts of climate change are not mitigated [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Precipitation can alter the occurrence of suitable larval habitats [ 22 , 24 , 25 ] and the viability of eggs and larvae [ 26 ]. Humidity can affect the mating, dispersal, longevity, bloodfeeding behaviors, and oviposition of mosquitoes [ 3 , 27 , 28 ]. However, there are numerous mitigating factors that can drastically alter mosquito population dynamics (e.g., forest cover), and the combined effects of multiple abiotic and biotic factors are often challenging to resolve.…”
Section: Introductionmentioning
confidence: 99%
“…In dry atmospheric conditions, mosquitoes desiccate easily resulting in depletion of adult vectors. A relative humidity of at least 50 to 60% ensures prolonged mosquito survival and breeding sites for the mosquitoes to lay eggs (Asgarian et al, 2021). Furthermore climatic variables alter interactions among the mosquito species and subsequently result in an increase or decrease of their population in particular areas (Weicheld, 2015).…”
Section: Introductionmentioning
confidence: 99%